Contribution of Islamic Personality in Increasing Work Ethic in Business/Industrial World - Efendi Efendi; Isa Anshori (Universitas Muhammadiyah Sidoarjo, 2018)
The educational process organized by Muhammadiyah schools has a large role in shaping the work ethic, which is of course by shaping the Islamic personality of the students. The main problems in this study are, (a) How is the formation of Islamic personality to improve the work ethic of students carried out at SMK Muhammadiyah 2 Taman _ Sidoarjo, (b) how the contribution of the formation of Islamic Personality in improving the work ethic of students during the Field Work Practice at DU / DI organized by SMK Muhammadiyah 2 Taman Sidoarjo. The purpose of this study is to describe and understand: (a). Implementation of the formation of Islamic personality to improve the work ethic of students while carrying out Field Work Practices in DU / DI organized by SMK Muhammadiyah 2 Taman - Sidoarjo, (b). Contributions to the formation of Islamic personality in improving the work ethic of students in the implementation of Field Work Practices in DU / DI for SMK Muhammadiyah 2 Taman-Sidoarjo.This study uses a qualitative type with a phenomenological approach, the research subject is determined purposively, namely 164 grade XI students who are currently doing Job Training. Derived from the majors of Electric Power Installation Engineering, Machining Engineering, Light Vehicle Engineering, and Multi Media. Data collection techniques using observation, interviews and documents. Data that has been collected is analyzed through data reduction, display and drawing conclusions.